Intake of snacks containing curcumin stimulates erythropoiesis and antioxidant response in dogs - Campigotto G.* (2020)
© 2020, Springer-Verlag London Ltd., part of Springer Nature.The objective of this study was to determine whether snacks containing curcumin have beneficial effects on dog health. The snacks were produced from commercial canned meat for dogs, and curcumin was added and homogenized. Snacks containing 15 mg of curcumin were produced, frozen, and offered to dogs twice a day. Ten beagles (6 months of age) were used. The animals were placed in an experimental kennel and allocated randomly to 1 of 2 treatments (5 dogs/treatment): snacks containing curcumin (curcumin; 30 mg of curcumin/animal/day) or not (control). On day 15, numbers of erythrocytes and hematocrit were greater in dogs fed with curcumin than in control dogs. Dogs fed with curcumin had lower numbers of leukocytes (day 30), neutrophils (day 15), and lymphocytes (day 30) than did control dogs. Dogs fed with curcumin had lower plasma levels of nitric oxide, reactive oxygen species, lipoperoxidation, and protein carbonylation on day 30 than did control dogs. Finally, dogs fed with curcumin had greater plasma total antioxidant capacity and concentrations of protein thiol, non-protein thiol, glutathione peroxidase, and superoxide dismutase on day 30 compared with control dogs. We conclude that curcumin in dog snacks stimulated the antioxidant system and consequently reduced oxidative reactions, which is beneficial to animal health. Furthermore, 30 mg of curcumin/dog/day reduced leukocyte counts, which suggests mild anti-inflammatory effects.